MEDIA SOSIAL BROADCAST SEBAGAI MULTIMEDIA TERINTEGRASI INDUSTRI KREATIF BAGI DIGITAL NATIVE GENERASI Z - Eko Hadi Prayitno; Nurul Giswi Karomah; Badriyah Badriyah (POLITEKNIK LP3I JAKARTA, 2021)
This study aims to determine the Z generation digital native of Instagram social media account owners with public features that have a tendency to develop integrated account owners, through the use of multimedia broadcasts and the potential to promote visual works in the creative industry. The data collection period was observed by observing the posting of the respondent's portfolio on the feed from May - September 2020. The research design was correlational quantitative research between the Characteristics of Generation Z (X1), Social Media Broadcast (X2) and Creative Industry Integrated Development Multimedia (Y) variables. The purpose of this study was to determine the relationship between the ability of Generation Z Characteristics in processing learning outcomes with the use of social media. Broadcast is integrated into a part of promoting portfolios in Creative Industry Integrated Development. Research data from a population of 180, of which there are 91 generation Z, and 20 accounts with Digital Native characteristics with public settings, taken as the research sample. The results obtained 1) Generation Z tends to have Digital Native Characteristics obtained as much as 84%, 2) Generation Z tends to have digital native characteristics that carry out the activity of Social Media Broadcast as much as 84%, 3) There is a native digital indicator of Generation Z doing Integrated Creative Industry Development for 88%. 4) Producing an accredited national publication research journal indexed.Keywords: Sosial Media broadcast, Multimedia, Creative Industry, Digital Native, Z Generation